2021
DOI: 10.3390/microorganisms9091836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plant Origin Essential Oils as Herbal Biocides for the Protection of Caves Belonging to Natural and Cultural Heritage Sites

Abstract: The present study concerns the serious issue of biodeterioration of the caves belonging to natural and cultural heritage sites due to the development of various microorganisms. Thus, a series of 18 essential oils (EOs) extracted from various Greek plants were evaluated in vitro (concentrations of 0.1, 0.2, 0.5, 1.0 and 5.0% v/v) against 35 bacterial and 31 fungi isolates (isolated from a Greek cave) and the antimicrobial activity was evident through the changes in optical density of microbial suspensions. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…This result is in agreement with other studies [69] that already demonstrated the broad biocidal action spectrum of such compound towards several microorganisms, such as fungi, bacteria, cyanobacteria and algae, found on various cultural heritage materials [54,[72][73][74]. As an example, a study of Argyri et al (2021) [75] tested eighteen high-quality essential oils from Greece, including extracts from Salvia sp., Foeniculum sp., Satureja sp, Juniperus sp., Citrus sp., Laurus sp. and Origanum sp., against 35 bacterial and 31 fungi isolated from a Greek cave, and the better results were obtained for both the EOs from O. vulgare, which inhibited the growth of all the strains at very low concentrations (0.1% v/v).…”
Section: Discussionsupporting
confidence: 90%
“…This result is in agreement with other studies [69] that already demonstrated the broad biocidal action spectrum of such compound towards several microorganisms, such as fungi, bacteria, cyanobacteria and algae, found on various cultural heritage materials [54,[72][73][74]. As an example, a study of Argyri et al (2021) [75] tested eighteen high-quality essential oils from Greece, including extracts from Salvia sp., Foeniculum sp., Satureja sp, Juniperus sp., Citrus sp., Laurus sp. and Origanum sp., against 35 bacterial and 31 fungi isolated from a Greek cave, and the better results were obtained for both the EOs from O. vulgare, which inhibited the growth of all the strains at very low concentrations (0.1% v/v).…”
Section: Discussionsupporting
confidence: 90%
“…Bacterial suspension of 100μL (0.5 MacFarland) was pipetted from 1 st to 11 th wells each then optical density of micro-titration plate was taken at 630nm at 0 time and 24 hours after the incubation at 37°C. After this, the same MIC procedure was repeated for E. globulus fractions in n-hexane, chloroform, n-hexane + chloroform and ethyl-acetate organic solvents (Argyri et al, 2021).…”
Section: Minimum Inhibitory Concentration (Mic) Of Plant Essential Oilsmentioning
confidence: 99%
“…Therefore, the potential antibacterial and antifungal properties of these oils are of great importance in many different applications [12]. It was recently established that certain EOs are effective antimicrobials against bacterial and fungal isolates from the Petralona Cave [13]. This cave is a karst formation found on the Chalkidiki peninsula in Greece, 300 m above sea level, one mile east of the settlement of Petralona, and 55 km from Thessaloniki [14,15].…”
Section: Introductionmentioning
confidence: 99%